Factors Influencing The Preference Of Customers Towards Islamic Banking: Evidence From Malaysia - Dawami, Qosdan (Journal of Islamic Economic Laws, 2020)
The purpose of this research is to investigate the pivotal determinants influencing the consumer’s preference towards the products and services of Islamic banking, apart from reviewing previous studies that considered perceived religiosity has an intense relationship with the individual’s intention and attitude. Moreover, this study also examines the direct relationship between the preference of customers and the Service Quality offered by Islamic banks. This study utilizes quantitative approach through conducting a survey to 60 students of International Islamic University Malaysia from various departments. Correlation and regression will be applied for data analysis. The result of the study indicated that the Attitude and the Service Quality offered by Islamic banks are the major determinants influencing the customers’ behaviour towards Islamic banking. On the other hand, the Image of the bank and the Religiosity were determining insignificantly to the intentions of customers to choose its products and services.